Dukungan Vanuatu Terhadap Kemerdekaan West Papua: Tinjauan Konstruktivisme Holistik - Hanafi, Muhammad Riza; Annahda, Isnin Nabila (Andalas Institute of International Studies UNAND, 2022)
Vanuatu is one of several Melanesian countries that has been consistently supporting the independence of West Papua. Vanuatu's stance is a form of Melanesian solidarity against colonialism that based on a regional value known as Melanesian Way. Introduced by Bernard Narokobi, a Papua New Guinean philosopher and poet, Melanesian Way brought by several students of Vanuatu that studied at University of Papua New Guinean. This nationalist ideology then become the spirit or anti colonialization in Vanuatu. This ideology will be discussed in this article as identity that construct Vanuatu interest in supporting the independence of West Papua. This study applied a holistic constructivism approach to assessing how Vanuatu's identity can influence its stance in supporting West Papua’s independence from 2010-2019. From the two variables of holistic constructivism approach, the domestic and the systemic level, it was found that the domestic level had a bigger role in shaping Vanuatu's stance on West Papua’s independence. This means that Vanuatu's identity and interests are endogenously shaped in which corporate identity has a more important role than social identity.Keywords : Vanuatu, West Papua, Melanesian Way, Holistic Constructivism, identity